2020
DOI: 10.3390/cancers12010218
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Membrane Ca2+ ATPase Isoform 4 (PMCA4) Has an Important Role in Numerous Hallmarks of Pancreatic Cancer

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is largely resistant to standard treatments leading to poor patient survival. The expression of plasma membrane calcium ATPase-4 (PMCA4) is reported to modulate key cancer hallmarks including cell migration, growth, and apoptotic resistance. Data-mining revealed that PMCA4 was over-expressed in pancreatic ductal adenocarcinoma (PDAC) tumors which correlated with poor patient survival. Western blot and RT-qPCR revealed that MIA PaCa-2 cells almost exclusively express PMCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 77 publications
0
20
1
1
Order By: Relevance
“…PMCA has been shown to have an important role in cancer [ 157 , 158 , 231 ]. Overexpression of PMCA4 in PDAC correlates with poor prognosis, while siRNA knockdown of PMCA4 inhibited migration and apoptosis resistance in cultured PDAC cells [ 232 ]. In the breast, PMCA has an important role in the normal physiology and in tumorigenesis.…”
Section: Opportunities For Targeting the Ca 2+ mentioning
confidence: 99%
See 1 more Smart Citation
“…PMCA has been shown to have an important role in cancer [ 157 , 158 , 231 ]. Overexpression of PMCA4 in PDAC correlates with poor prognosis, while siRNA knockdown of PMCA4 inhibited migration and apoptosis resistance in cultured PDAC cells [ 232 ]. In the breast, PMCA has an important role in the normal physiology and in tumorigenesis.…”
Section: Opportunities For Targeting the Ca 2+ mentioning
confidence: 99%
“…This is particularly relevant because almost every Ca 2+ channel/transporter is exquisitely sensitive to pH, especially CRAC channels [ 268 , 269 ], and the acid-sensing Ca 2+ -permeable ion channels (ASICs) have important roles in both cancer cells [ 270 , 271 , 272 , 273 ] and immune cells [ 274 , 275 , 276 ]. Moreover, the acidic tumour microenvironment would be expected to impact Ca 2+ -signalling in both cancer cells [ 232 ] and immune cells [ 277 , 278 ] by promoting PMCA activity. This is because ATP-driven PMCAs are Ca 2+ /H + exchangers, and thus their Ca 2+ efflux activity is facilitated by extracellular acidification and inhibited by extracellular alkalinisation [ 279 , 280 ].…”
Section: Calcium Signalling and The Tumour Immune Microenvironmentmentioning
confidence: 99%
“…Differences between the aggregated contact maps between clusters were then used to assess unique translocation and inversion events across the sampled cells. We found that our single-cell contact data uncovers an intrachromosomal translocation between the 8.5-9.5 Mbp and 88.5-91.0 Mbp regions of chromosome 12 (Figure 2k), containing ATP2B1, which is commonly overexpressed in PDAC 30 and the tumor suppressor gene DUSP6 31 that is only present in PDAC-1.…”
mentioning
confidence: 83%
“…However, the alternate splicing of this gene mRNA transcripts results in a diverse array of more than 30 splice variants. These isoforms are expressed in different areas of the body: PMCA2–3 are “rapid response pumps” expressed in excitatory cells like muscle cells; PMCA1–4 are ubiquitous throughout all tissues in humans, while PMCA4 seems to have a specific role in proliferative signaling, NF-κB nuclear translocation, tumor necrosis factor (TNF)-induced cell death and migration, which all are important pathways for the cancer hallmarks conservation [ 17 ].…”
Section: Ca 2+ Transporters In Pdacmentioning
confidence: 99%